O processo de internacionalização de uma marmoraria brasileira e seus impactos na cadeia de operações - Meyer, Luís Augusto (2014)
In competitive environments and when the economic conditions are favorable, entrepreneurial movements are more frequent and contribute to growth trends for markets and nations. Organizations from “emerging” countries, which break national barriers in an attempt to grow even further in new markets, demonstrate the relationship that exist between economic prosperity and the positive expectations of the entrepreneur, even when faced with challenges concerning the increase in complexity of the supply chain and higher logistics costs. Based on a qualitative research with an organization belonging to the marble industry, this study tries to identify the reasons that influence the international expansion movement of the organization, how it happened, what the challenges were and the achieved results, analyzing if the main internationalization theories helped understand the phenomenon, with a special focus on the organization’s supply chain. Results show that the internationalization process did affect the organization’s supply chain and its overall operation, but the form it happened was very dependent of the decision style of the entrepreneur and the way he dealt with the corporate strategic process.